Cosmeceutical Potential of the Green Macroalga Caulerpa Prolifera - Rosa, Gonçalo P. (2022)
The present cosmeceutical industry has been gradually shifting its interest from products based on synthetic compounds to macroalgae-based products due to their interesting antiaging properties but also to their lower cytotoxicity and allergens content. Molecules isolated from macroalgae already showed potential as either active cosmetic ingredients or key elements for the consistency of the cosmetic formulation. In this regard, it is of foremost importance to keep studying the chemical composition of different algal species, aiming to find new compounds with cosmeceutical potential. […].